Application of Video Based Learning Media to Increase Interest in Learning Social Sciences - Tastury*, Nabila; Nurasiah, Nurasiah; Azis, Abdul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
His research was conducted with the aim of finding out the application of video based learning media in social studies learning and students' interest in the application of video based learning media. This research used descriptive qualitative research methods. The instruments used in collecting research data used observation sheets and questionnaires. The subjects in this research were students in class VIII-A at SMP Negeri 1 Ingin Jaya, totaling 25 students. Based on the results of the observation sheet, it was found that the implementation of video based learning media was 88% and based on the questionnaire sheet, the results showed that student interest in the application of video based learning media was 82.16% These results explain that the application of video based learning media can increase students' interest in learning social studies in class VIII of SMP Negeri 1 Ingin Jaya.